The neuromodulation casebook - Arle, Jeffrey E. (Academic Press, an imprint of Elsevier, 2020)
The Neuromodulation Casebook is a case-based volume for practical, hands-on decision-making using realistic case examples from the field of neuromodulation. It encompasses a variety of techniques and therapies, ranging from deep brain stimulation for a multitude of disorders, to spinal cord stimulation, peripheral nerve stimulation, cortical stimulation and cranial nerve stimulation, as well as non-invasive therapies and other implanted types of devices that interface with the nervous system. Allowing readers to better learn via case-based examples, this practical volume depicts real examples of decisions neuroscientists and neurosurgeons need to make every day from leaders in the field. This book serves as a companion text to the editor's previous titles Essential Neuromodulation and Innovative Neuromodulation for neuroscience, neural engineering and biomedical engineering courses. -- Publisher.